Extremity Ischemia After Jellyfish Envenomation: A Case Report and Systematic Review of the Literature - Saif, Badran (2022)
BackgroundExtremity ischemia and necrosis after jellyfish envenomation can be mutilating and cause long-term functional deficits. The best way to manage these presentations is unknown. ObjectiveThe aim of this review was to establish an evidence-based consensus for the management of extremity ischemia after jellyfish envenomation. MethodsA systematic review of cases of extremity ischemia and necrosis after envenomation by marine cnidarians was performed to clarify what is and what is not known about management and outcomes, to draw conclusions about how best to manage these rare presentations, and to establish an evidence-based algorithm. ResultsThe ischemic sequelae of envenomation typically evolves over a few days. Close medical supervision is necessary to react promptly to the evolving clinical scenario. In the literature, 15 different pharmacologic classes have been used to manage these presentations. Only IV infusions of prostaglandin derivatives and intra-arterial thrombolytics have been found to improve the clinical picture and avoid the need for surgical fasciotomy and debridement in some cases. Anticoagulants, antiplatelet agents, steroids, antibiotics, and nitrates, which are among the most commonly prescribed pharmacologic agents, have not been observed to alter the clinical picture. ConclusionsSurgery for compartment syndrome and necrosis are common sequelae of extremity envenomation by marine cnidarians. Only prompt use of IV prostaglandins or intra-arterial thrombolytics can halt ischemic progression and avoid the need for surgery. An algorithm is proposed to guide management of these rare and mutilative presentations.